Search for deconfinement in NA49 at the CERN SPS - Seyboth, Peter (Array, 2003)
Experiment NA49 at the Cern SPS uses a large acceptance detector for a systematic study of particle yields and correlations in nucleus-nucleus, nucleon-nucleus and nucleon-nucleon collisions. Preliminary results for Pb+Pb collisions at 40, 80 and 158 A*GeV beam energy are shown and compared to measurements at lower and higher energies.